Komunikasi Informasi Edukasi (KIE) Kesehatan Reproduksi Remaja (KRR) pada Masa Pandemi Covid 19 di SMP N 1 Dukuhwaru Kab. Tegal - Ike Putri Setyatama; masturoh masturoh; siswati siswati; Adrestia Rifki Naharani (JABI: Jurnal Abdimas Bhakti Indonesia, 2022)
The large population of the world's population is teenagers and the progress of a nation can be seen, one of which is the behavior of teenagers. The adolescent period is a transition from childhood to adulthood, where the process of sexual maturity begins. Physical and psychological changes in adolescents lead to attraction to peers of the opposite sex, so that adolescents are prone to unhealthy behavior, this incident in adolescents requires early education related to healthy reproductive health in adolescents Teenager Based on studies at SMP N 1 Dukuhwaru, there are several problems related to knowledge of adolescent reproductive health, including the lack of knowledge about personal hygiene, changes in the physiology of the adolescent reproductive system, and the psychology of puberty and related to menstruation and various problems. In accordance with the partner's problem, the community service team carried out community service activities for students at SMP N 1 Dukuhwaru, as an effort to apply service in the implementation of the Tri Dharma of Higher Education. Technical implementation of this community service with promotive efforts, including communication, information and education (KIE) activities related to adolescent reproductive health with material presentations followed by reviews, discussions and questions and answers. In the activity of providing material, in addition to being given visually with pictures and videos, material is also provided with props, especially the material for cleaning and caring for reproductive organs. The results of the implementation of service include students of SMP N 1 Dukuhwaru having correct knowledge related to reproductive health, namely the ability to describe and explain personal hygiene, changes in the physiology of the adolescent reproductive system, psychology of puberty and menstruation related to various problems and solutions or ways to overcome them. With the enthusiasm of the target participants, the school hopes that similar activities can be carried out regularly at SMP N 1 Dukuhwaru